2015
DOI: 10.3758/s13421-015-0529-z
|View full text |Cite
|
Sign up to set email alerts
|

Deadlines in space: Selective effects of coordinate spatial processing in multitasking

Abstract: Many everyday activities require coordination and monitoring of multiple deadlines. One way to handle these temporal demands might be to represent future goals and deadlines as a pattern of spatial relations. We examined the hypothesis that spatial ability, in addition to executive functioning, contributes to individual differences in multitasking. In two studies, participants completed a multitasking session in which they monitored four digital clocks running at different rates. In Study 1, we found that indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 85 publications
(101 reference statements)
4
30
0
Order By: Relevance
“…As a direct support for this spatial offloading hypothesis, we have reported several studies (with Swedish and Italian participants) showing that spatial ability and executive functioning are independent predictors of multitasking performance, and that spatial ability predicts multitasking over and beyond executive functioning (Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, & Mäntylä, 2014;Todorov, Del Missier, Konke, & Mäntylä, 2015).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…As a direct support for this spatial offloading hypothesis, we have reported several studies (with Swedish and Italian participants) showing that spatial ability and executive functioning are independent predictors of multitasking performance, and that spatial ability predicts multitasking over and beyond executive functioning (Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, & Mäntylä, 2014;Todorov, Del Missier, Konke, & Mäntylä, 2015).…”
mentioning
confidence: 64%
“…Multitasking performance was based on a combined score of the four counter tasks (see also Todorov et al, 2015), with response accuracy and monitoring frequency as dependent measures. A response was considered correct if the spacebar was pressed within 1 digit of the target (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we propose, as in Norman and Shallice's (1986) supervisory attentional system, that learned spatial schemas (or schemata, in Norman and Shallice's theory) enable people to be less dependent on attentional resources. Recent results by Mäntylä and colleagues (e.g., Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, Konke, & Mäntylä, 2015;Todorov, Kubik, Carelli, Del Missier, & Mäntylä, 2018) seem compatible with this idea. They showed that spatial abilities contribute to multitasking, and that when spatial coding was impeded, multitasking performance dropped.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 79%
“…We have recently suggested that one way to reduce these executive control demands is to represent the temporal pattern of deadlines and task goals in spatial terms (Mäntylä 2013; Mäntylä and Todorov 2013; Todorov et al 2014; Todorov et al 2015). Indirect support for this spatiotemporal view of multitasking is provided by behavioral and neurocognitive studies demonstrating that we understand and handle aspects of time (e.g., duration, sequence) by representing them in a spatial reference frame (for similar views, see, e.g., Bonato et al 2012; Casasanto and Boroditsky 2008; Dehaene and Brannon 2011).…”
Section: Introductionmentioning
confidence: 99%